Integration of Javanese Rumangsa Handarbeni Pitutur Luhur Values in Biblioeducation to Develop Empathy of Education Students - Prasetyani, Yohana; Indreswari, Henny; Rahman, Diniy Hidayatur (Jurnal Paedagogy, 2023)
This study aims to analyze the integration of Rumangsa Handarbeni’s values with empathy, then poured into guidance counseling services, a biblioeducation that aims to develop empathy for educational students. This research was conducted using qualitative methods and literature studies by examining books, journals, and other literature that follow the theories discussed, especially in the scope of guidance and counseling. All scientific articles created were sourced from Scopus, DOAJ, and Google Scholar. Furthermore, related data was collected, recorded, and analyzed descriptively and qualitatively. The research results obtained that the Javanese value of Rumangsa Handarbeni’s Pitutur Luhur was closely related to the aspect of empathy, where empathy is the attitude of being able to feel what others are feeling but remain in a position, which can be integrated into a guidance and counseling service to develop empathy, one of which is biblioeducation. In the biblioeducation, the stories presented are internalized from the values of the pitutur luhur Rumangsa Handarbeni. With this service, it is hoped that can open a new perspective on empathy for students, especially education students who are prepared to become prospective educators.